Greying the Budget: Ageing and Preferences over Public Policies - Luiz de Mello; Simone Schotte; Erwin R. Tiongson; Hernan Winkler (Institute for the Study of Labor (IZA), 2016)
This paper looks at how individual preferences for the allocation of government spending change along the life cycle. Using the Life in Transition Survey II for 34 countries of Europe and Central Asia, we find that older individuals are less likely to support a rise in government outlays on education and more likely to support increases in spending on pensions. These results are very similar across countries, and they do not change when using alternative model specifications, estimation methods and data sources. Using repeated cross-sections, we control for cohort effects and confirm our main results. Our findings are consistent with a body of literature arguing that conflict across generations over the allocation of public expenditures may intensify in ageing economies.
Keywords: H3; H5; J14; 330; ageing; public spending; cohort effects